Pemberdayaan Kader dengan Meningkatkan Pengetahuan dan Keterampilan Kader di Wilayah Kerja Puskesmas Bayat - pratiwi, yuyun, Arif Widodo, A.Kep., M.Kes (2017)
Posbindu a health service activities involving community participation in both cadres, organizations, community groups and religious. Posbindu organizing activities by and for the people especially cadres. Posbindu cadres role in the conduct of a very dominant because health workers only as a companion and reference receiver, so that the knowledge and skills of cadres should be improved. The Research quantitative methods to the type of quasy experimental design. The researchpretest and posttest control group design. This study population all cadres of health in the Region Health Center Bayat, Klaten totaling 60 people, samples were taken 60 people to 30 people in the treatment group and the control group of 30 people with a total sampling technique. The independent variable in the form of empowerment cadres while the dependent variable knowledge and skills, the instrument used by the questionnaire. Data analysis techniques paired with a simple test and independent simple paired t-test. The results showed that the respondents 'knowledge of the experimental group and the control group before being granted the empowerment cadres in service Posbindu in enough category (77.8% and 82.4%) and the respondents' knowledge experimental group and the control group after given empowerment cadres in service Posbindu in enough categories (55.6% and 70.6%), respondents skills experimental group and the control group before being granted the empowerment cadres in service Posbindu the skilled category (72.2% and 82.4%) and skills respondent experimental group and the control group after given empowerment cadres in service Posbindu the skilled category (61.1% and 70.6%), and there are significant empowerment Posbindu cadres in the service of the knowledge and skills of cadres in service in Puskesmas Posbindu Bayat (p = 0.014, p = 0.019) , Suggested for cadres, after Posbindu empowerment in the service, people can change the skills to be no decline in service Posbindu. One of them with the empowerment of the cadres Ponbindu.